Moiré excitons in MoSe2-WSe2 heterobilayers and heterotrilayers - Michael Förg; Anvar S. Baimuratov; Stanislav Yu. Kruchinin; Ilia A. Vovk; Johannes Scherzer; Jonathan Förste; Victor Funk; Kenji Watanabe; Takashi Taniguchi; Alexander Högele (Nature Communications, 2021)
Here, the authors show that the photoluminescence of MoSe2/WSe2 heterobilayers is dominated by valley-direct excitons, whereas, in heterotrilayers, interlayer hybridization turns momentum-indirect interlayer excitons into energetically lowest states with phonon-assisted emission.